1980
DOI: 10.1111/j.1748-5827.1980.tb01366.x
|View full text |Cite
|
Sign up to set email alerts
|

A 37XO chromosome complement in a kitten

Abstract: In two kittens from the same litter with spina bifida and meningocoele the phenotypic male was found to have a normal 38XY chromosome complement whilst the phenotypic female had a 37XO chromosome complement. It was concluded that the spina bifida condition was due to the manx ancestry and not to the 37XO karyotype. The possible effect of the XO complement in cats is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1983
1983
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The first case of X monosomy in a kitten with coarctation of the aorta was presented by Norby et al (1974). In the second case, a single cell line (37,X) was identified in a cat with spina bifida, but this malformation was not related with the X monosomy (Long and Berepubo 1980). The third case it was a small Burmese cat with primary anestrus and ovaries containing inactive germinal epithelium only (Johnston et al 1983).…”
Section: Introductionmentioning
confidence: 99%
“…The first case of X monosomy in a kitten with coarctation of the aorta was presented by Norby et al (1974). In the second case, a single cell line (37,X) was identified in a cat with spina bifida, but this malformation was not related with the X monosomy (Long and Berepubo 1980). The third case it was a small Burmese cat with primary anestrus and ovaries containing inactive germinal epithelium only (Johnston et al 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Three cases of feline 37,X have been reported, 2 of which died by 3 days of age [Norby et al, 1974;Long and Berepubo, 1980]. Normal ovarian histology was reported in one of these [Norby et al, 1974].…”
Section: Monosomy X and Variantsmentioning
confidence: 99%
“…Phenotypic male cats with a 39,XXY karyotype or its mosaic variants 38,XY/39,XXY and 38,XY/39,XYY [Centerwall and Benirschke, 1975;Moran et al, 1984;Leaman et al, 1999;Schmidt-Küntzel et al, 2009;Pedersen et al, 2014] as well as tomcats with 38,XX/38,XY chimeric karyotypes [Centerwall and Benirschke, 1975;Moran et al, 1984;Leaman et al, 1999;Long, 1999] may only be found if they have unusual tortoiseshell or calico coats. Cats with monosomy X and variants as well as XXX and variants are phenotypic fe-males [Norby et al, 1974;Long and Berepubo, 1980;Johnston et al, 1983;Manna and Sarkar, 1988]. Pregnancy and unilateral ovarian dysgenesis were reported in 2 queens with the mosaic karyotypes 37,X/38,XX and 37,X/39,XXX [Dybdahl Thomsen et al, 1987].…”
Section: X/38xy Mosaicism In a Cryptorchidmentioning
confidence: 99%